2005
DOI: 10.1016/j.autneu.2005.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise intensity, posture, pressure on the back and ambient temperature on palmar sweating responses due to handgrip exercises in humans

Abstract: We have, by using newly developed ratemeters, attempted to examine the effects of exercise intensity, posture, pressure on the skin of the back, and ambient hyperthermic conditions (~30 °C) on the 5-s handgrip exercise-mediated responses of active palmar sweating in humans.Thirty-five right-handed male (n=5) and female (n=30) important that subjects maintain a constant handgrip force and posture and that ambient temperature be kept under normothermic conditions. 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Synchronous electrodermal activity was observed in the 1970's by Ogawa et al (10)(11)(12)29), followed by other authors as Ohhashi (24,30), Machado-Moreira and Taylor (25), and Tronstad et al (31).…”
Section: Discussionmentioning
confidence: 92%
“…Synchronous electrodermal activity was observed in the 1970's by Ogawa et al (10)(11)(12)29), followed by other authors as Ohhashi (24,30), Machado-Moreira and Taylor (25), and Tronstad et al (31).…”
Section: Discussionmentioning
confidence: 92%
“…To see whether a sweat secretion problem existed on the lesional area of the skin, palmar sweat volume was measured using a cutaneous evaporation meter (portable sweat meter TS-100; TECHNO SCIENCE, Tokyo, Japan) according to the ventilation capsule method (Tomioka et al, 2005;Ohshima et al, 2008), and was compared with nonlesional areas. Probe (1 cm 2 ) of the sweat meter was applied on the target skin area, and the 2-minute sweat volume was measured at both the lesional and nonlesional areas on the palms of the PPP patients.…”
Section: Sweat Measurementmentioning
confidence: 99%
“…It is known that the hand grip exercise induces sweating of the contralateral hand. That reaction is used to determine therapeutic effects on hyperhidrosis, and the measurement method is the ventilated capsule method 27,28 . In the measurement by OCT, it has been reported that the mean volume of acrosyringia of healthy subjects was increased by the handgrip exercise 23,24 .…”
Section: Discussionmentioning
confidence: 99%